If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -12x + 76 = 2x + 6 Reorder the terms: 76 + -12x = 2x + 6 Reorder the terms: 76 + -12x = 6 + 2x Solving 76 + -12x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 76 + -12x + -2x = 6 + 2x + -2x Combine like terms: -12x + -2x = -14x 76 + -14x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 76 + -14x = 6 + 0 76 + -14x = 6 Add '-76' to each side of the equation. 76 + -76 + -14x = 6 + -76 Combine like terms: 76 + -76 = 0 0 + -14x = 6 + -76 -14x = 6 + -76 Combine like terms: 6 + -76 = -70 -14x = -70 Divide each side by '-14'. x = 5 Simplifying x = 5
| 9x-10y-4=0 | | 3m+n-20m+13n= | | 2t^2+9t-5=0 | | 10=7+t | | 4-3x+11= | | -6x^2=1 | | 6x^2=1 | | 30=12+t | | (.25)x+2=4-(.5)x | | 21+7x=105 | | 3.167x=4x-4 | | ax+bx-1=8 | | 3*6+3*5= | | 30*7=t | | 5x-6=13-x | | 18p^2-77p-18=0 | | 30t=7 | | 9(3x+10)=2x+340 | | 10=5t+10 | | 21+7x=19 | | 3.6+3.5= | | 3(x-2)=5(4+x) | | 2x^2-4x-18=0 | | 50(x-1)=36x | | -3=k+75 | | (-15)=3x+(-63) | | 5c-7=37 | | 7t=30 | | 6-3+5= | | 5z+6=-2 | | 49+100=o^2 | | 210=70t |